Influenza virus causes lung immunopathology through down-regulating PPARγ activity in macrophages - Zhang, Hongbo; Alford, Taylor; Liu, Shuangquan; Zhou, Dongming; Wang, Jieru (Frontiers in Immunology, 2022)
Fatal influenza virus infection often activates too many inflammatory signals, sometimes leading to multi organ failure and death, also referred as cytokine storm. PPAR-γ agonists are well known as candidates for cytokine storm modulation. In the present study, we identified that influenza infection not only reduced PPARγ expression but also decreased PPARγ transcription activity in human alveolar macrophages (AMs) from different donors. Treatment with PPARγ agonist Troglitazone significantly ameliorated virus-induced proinflammatory cytokine secretion but did not interfere with the IFN-induced antiviral pathway in human AMs. In contrast, PPARγ antagonist and knockdown of PPARγ in human AMs further enhanced virus-stimulated proinflammatory response. In a mouse model of influenza infection, flu virus dose-dependently reduced PPARγ transcriptional activity and decreased expression of PPARγ. Moreover, PPARγ agonist troglitazone significantly reduced high dose of influenza infection induced lung pathology. In addition, flu infection reduced PPARγ expression in all mouse macrophages including AMs, interstitial macrophages, and bone-marrow-derived macrophages but not in alveolar epithelial cells. Our results indicate that influenza virus specifically targets PPARγ pathway in macrophages to cause acute injury to the lung.